Mars Life: Now - Legacy Timeline - Ma, Stacey (My University, 2025)
The final project in Typography 2 engages students in a “choose your own adventure” learning experience. Students read a novel, interview the author, and then decide what design piece to create to communicate the content of the book. A gossip magazine, tickets to Mars, Martian Kush kit, plastic companion plants, collectible figurines, a boardgame where nobody wins, and a welcome Martian baby package, are among the thought-provoking, creative, unique, and “out of this world” pieces created for this year’s book, “Girlfriend on Mars”, by award-winning author Deborah Willis.
Exhibited April 10 – May 11, 2025, on the Digital Wall at MacEwan University Library in Edmonton, Alberta.
Keywords: MacEwan Book of the Year; choose your own adventure; design piece; Girlfriend on Mars